VOCATIONAL EDUCATION INTEGRATED TO SECONDARY SCHOOL AT A FEDERAL INSTITUTE IN THE NORTH OF BRAZIL: CONTRADICTIONS AND PERSPECTIVES - das Neves, Cristiane das Neves (European Scientific Journal, ESJ, 2014)
Held at the Federal Institute of Education, Science and Technology of Acre, the research aimed to identify the perception of the course of 44 students and 13 teachers from 4 classes of Technical Vocational Education in Middle Level Integrated to computer science of Câmpus Rio Branco, during the academic year of 2013, through questionnaires with five questions. The apparent lack of motivation among students proved to be dissatisfaction with the organizational structure. Teachers agreed that reform is paramount in the course offered.